2016
DOI: 10.3390/ijgi5120241
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Transition Rules for Cellular Automata Using Artificial Bee Colony and Particle Swarm Optimization Algorithms in Urban Growth Modeling

Abstract: This paper presents an advanced method in urban growth modeling to discover transition rules of cellular automata (CA) using the artificial bee colony (ABC) optimization algorithm. Also, comparisons between the simulation results of CA models optimized by the ABC algorithm and the particle swarm optimization algorithms (PSO) as intelligent approaches were performed to evaluate the potential of the proposed methods. According to previous studies, swarm intelligence algorithms for solving optimization problems s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In recent years, intelligent algorithms have emerged endlessly, and learning models are widely applied to urban CA modeling. It can be found in many studies that the simulation accuracy of learning models is often higher than that of statistical models (Basse et al, 2014; Naghibi and Delavar, 2016; Feng and Liu, 2013; Zhang and Wang, 2022), which leads to the pursuit of learning models and the neglect of statistical models. Nowadays, the available earth system data and its transmission, processing, and application are increasing geometrically (Reichstein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, intelligent algorithms have emerged endlessly, and learning models are widely applied to urban CA modeling. It can be found in many studies that the simulation accuracy of learning models is often higher than that of statistical models (Basse et al, 2014; Naghibi and Delavar, 2016; Feng and Liu, 2013; Zhang and Wang, 2022), which leads to the pursuit of learning models and the neglect of statistical models. Nowadays, the available earth system data and its transmission, processing, and application are increasing geometrically (Reichstein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…km to 9.6 million sq. km for Urmia, Iran [49] and mainland China [46] respectively. It's also found that most researchers have calibrated 10 to 20 years of spatial and non-spatial data and forecasted for 10 to 40 years having a resolution of 30 m by using neighborhood window sizes varying from 3x3 m [10] to 11x11 m. [50] Delicate resolution data and window size 5x5 have given satisfactory results, [12,51]…”
Section: Discussionmentioning
confidence: 99%
“…The Artificial Bee Colony (ABC) algorithm is a one of the most used metaheuristic search algorithms for optimizing many different real world problems such as transportation, engineering design, scheduling analysis, cost optimization, and logistic planning, as well as the optimization method (Naghibi and Delavar, 2016). ABC is recently developed by Karaboga in 2005, and it was applied to different problems by many researchers (Karaboga, 2005;Karaboga and Basturk, 2008;Karaboga and Akay, 2011;Karaboga et al, 2014;Szeto and Jiang, 2012;Naghibi and Delavar, 2016;Sonmez et al, 2017;Yao et al, 2017). ABC algorithm is inspired by the intelligent foraging behavior of honey bees, and it is mainly based on foraging behaviors of honey bee swarms in their daily life, and the main steps and behaviors of the bees in the algorithm are given below (Figure 4).…”
Section: Modeling Of Boarding Times Using Abc Algorithmmentioning
confidence: 99%